Case Report: A Chinese child with Barth syndrome caused by a novel TAFAZZIN mutation - Che, Mingxuan; Li, Fuhai; Jia, Yaning; Liu, Qingzheng; Hu, Jian; Zhang, Jidong; Liu, Shiguo (Frontiers in Cardiovascular Medicine, 2024)
Barth syndrome (BTHS) is a rare X-linked recessive genetic disorder characterized by a broad spectrum of clinical features including cardiomyopathy, skeletal myopathy, neutropenia, growth delay, and 3-methylglutaconic aciduria. This disease is caused by loss-of-function mutations in the TAFAZZIN gene located on chromosome Xq28, resulting in cardiolipin deficiency. Most patients are diagnosed in childhood, and the mortality rate is highest in the early years [1] . We report a case of acute, life-threatening metabolic decompensation occurring one day after birth. A novel TAFAZZIN splice site mutation was identified in the patient, marking the first reported case of such a mutation in BTHS identified in China. The report aims to expand our understanding of the spectrum of TAFAZZIN mutations in BTHS.